Effects of dietary tuna dark muscle enzymatic hydrolysis and cooking drip supplementations on growth performance, antioxidant activity and gut microbiota modulation of Bama mini-piglets. Issue 43 (12th August 2019) - Zhou, Jun; Yang, Mingyuan; Han, Jiaojiao; Lu, Chenyang; Li, Ye; Su, Xiurong
Abstract : Experiments were conducted to evaluate the enzymatic hydrolysis of tuna dark muscle (EH-TDM) and cooking drip (EH-TCD) as nutrition supplements in Bama mini-piglets. Abstract : Experiments were conducted to evaluate the enzymatic hydrolysis of tuna dark muscle (EH-TDM) and cooking drip (EH-TCD) as nutrition supplements in Bama mini-piglets. Our results showed that EH-TDM treatment produce considerable benefits for the Bama mini-piglets in terms of the feed efficiency, the prevention of oxidative damage and the control of blood lipid levels. The EH-TCD treatment also improved the growth performance, whereas all other aspects deteriorated. The analyses of the gut microbiota revealed an increased proportion of bacteria involved in energy metabolism and protein utilization in these two groups. Furthermore, short chain fatty acid producing bacteria were increased, as well as the genera Lactobacillus and Bifidobacterium, which are involved in intestinal dysfunction regulation. This study will provide valuable information for the development of marine protein hydrolysates as feed ingredients for the swine industry.